Thermoelectric properties of Indium doped skutterudite thick film synthesized by a facile technique of electrochemical deposition - Nuur Syahidah Sabran; Iman Aris Fadzallah; Mohd Faizul Mohd Sabri; Takahito Ono (Journal of Materiomics, 2023)
Doped/filled skutterudites are much studied materials due to their excellent thermoelectric performance. However, their synthesis and preparation is complicated. This work synthesized indium (In) doped cobalt triantimonide (CoSb3) skutterudite thick films using a facile electrochemical deposition technique through chronoamperometric steps for 2 h. The nominal composition of In element is found in the range of 0.55–0.23 for a stoichiometric condition of In doped CoSb3 thick films. The early crystal growth of In doped films shows instantaneous nucleation and is controlled by the charge transfer process with diffusion coefficient, D of 10−5 cm2/s. The incorporation of In into the interstitial sites of CoSb3 cages is evident from the lattice constant (a) expansion as observed in XRD. The optimum Seeback coefficient (S) of the 0.5 mmol In doped CoSb3 thick film is −89.84 μV/K at 282 K, due to an increase in the carrier concentration (n ∼1020 cm−3). The negative S is due to the electron donor behaviour of the In. Meanwhile, high electrical conductivity, σ value (14.26 kS/m) contributes to a power factor (S2σ) increment of 115.11 μW/(m·K2). The result shows a promising thermoelectric property of doped skutterudite synthesized by electrochemical deposition technique.